(3JaSjQ CHj GddjK GdSeQbfOis - (3fUQ Hf eMeO Hf CMeO Hf EHQGgje GdSeQbfOj GdMfaj ,CHh GddjK,J (B373 (3g` s
(3ChdgG (B:s
(3bhdg JHGQc hJYGdi (B" (3jS (B" (3bQC MeRI Hjf GdcSQ hGdaJM , hbQC GdcSGFi HEeGdI hGdHGbhf HGdaJM s
(3BNQgG (B:s
(3ef GdLfI hGdfGS jYfi jONd ai UOhQ GdLf ceG jONd ai UOhQ GdEfS hjhShS dge hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B91 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B490s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B441s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs